The hospital and home use of a 30-second hand-held blood ketone meter: guidelines for clinical practice. - Wallace, T; Meston, N; Gardner, S; Matthews, DR (2001)
AIMS: To establish the role of the measurement of beta-hydroxybutyrate (beta-OHB) in distinguishing simple hyperglycaemia from ketosis, and as an indicator of adequate resolution of ketoacidosis, using an electrochemical blood ketone meter. The aim of the study is to assess the accuracy and precision of the meter and to develop clinical guidelines for the use of the ketone meter at home and in hospital. PATIENTS AND METHODS: Twenty patients with poor glycaemic control (mean HbA1c 10.2%) were recruited from the diabetes clinic and 14 patients admitted with diabetic ketoacidosis (DKA) were recruited from two Accident and Emergency Departments. The blood obtained at each routine fingerprick test for glucose measurement was tested for beta-OHB using the ketone meter. Plasma beta-OHB concentrations were also measured on admission using a laboratory enzymatic method. RESULTS: Paired glucose and beta-OHB meter readings (n = 1099) in clinic patients demonstrated that, in the absence of intercurrent illness, beta-OHB levels did not exceed 1 mmol/l, irrespective of glucose readings. In the 14 ketoacidotic patients, the mean plasma beta-OHB concentration, measured in the laboratory, on admission was 7.4 mmol/l (range 3.9-12.3 mmol/l). The median half-life of beta-OHB was 1.64 h (1st IQR 2.27 h, 3rd IQR 1.34 h). The median time taken, from the initiation of treatment, for beta-OHB concentrations to fall to below 1 mmol/l was 8.46 h (range 5-58.33 h). CONCLUSION: Near patient blood ketone testing is a useful adjunct to blood glucose monitoring in distinguishing between ketosis and simple hyperglycaemia. The data suggest that beta-OHB levels > or = 1 mmol/l require further action and levels > 3 mmol/l necessitate medical review. In addition, the rate of fall of beta-OHB in DKA can be used as an indicator of the adequacy of treatment.